Comparison and analysis of the biomechanics of the lower limbs of female tennis players of different levels in foot-up serve - Liang, Zhiqiang; Wu, Jinan; Yu, Jiabin; Ying, Shanshan; Liu, Zhiyong; Zhang, Yu; Gu, Yaodong; Li, Jianshe (Frontiers in Physiology, 2023)
In this study, we studied the biomechanics of lower limbs of female tennis players of different levels in foot-up serve (FUS). This study showed the differences among different levels of athletes in FUS and provided useful information for the optimization of athletes' movement technology. The experiment was carried out in the laboratory, and the biomechanical data of lower limbs of female tennis players at three levels were collected during FUS. Statistical analysis of the collected kinematic, dynamic, and spatiotemporal parameters was conducted by one-factor ANOVA. The following research results were drawn. (1) In the preparation stage of FUS, high movement performance was related to the range of motion of joints, the working mode of muscles, and the stiffness level of lower limbs during this period. Athletes’ lower limb stiffness and joint range of motion were also related to the safety and risk level of FUS in the landing buffer stage. (2) High-level athletes were better at improving sports performance and preventing injuries by adjusting joint ROM and lower limb stiffness than low-level athletes. Such control could be learned through training intervention.